Subrepresentación política de las mujeres en México 1976-2003. Diputadas del Congreso de la Unión y del Congreso del Estado de Jalisco - Diana Melchor Barrera (Les Cahiers ALHIM)
This work describes the underrepresentation of female deputies in Mexico between 1976 and 2003 since the revision of the integration of ten legislatures of the Chamber of Deputies of the Congress of the Union and the Congress of the State of Jalisco. This uses the concept of spatial justice that part of pointing out that geographies of spatial discrimination produce structures of unequally distributed pros or disadvantages that can affect the lives of individuals (Soja, 2014:49), as well as the gender perspective from a descriptive quantitative analysis of information. This perspective allows to observe differences, similarities and inequalities between women and men (Lagarde, 2003: 9), as well as to analyze the social relationships that are based on sexual difference as a field of reproduction of gender inequality (Tepichin, 2016: 76). The quantitative approach examines information on data on federal and local councils, as well as the candidacies of Jalisco in the Official Newspaper El Estado de Jalisco, in the Archive of the Congress of the State of Jalisco and in sociodemographic reports prepared by the National Institute of Statistics and Geography.